Barriers to the utilization of primary care services for mental health problems among adolescents in a secondary school in Malaysia - Jaffar, Aida; Muhammad, Noor Azimah; A Rashid, Mohd Radzniwan; Mohd Daud, Tuti Iryani; Musa, Ramli; Omar, Khairani (Academy of Family Physicians of Malaysia, 2010)
Objective: To study the barriers toward the utilization of primary care services for mental health problems among adolescents in a secondary school in Hulu Langat, Selangor, Malaysia. Methods: This was a cross-sectional study conducted in July 2008 at a secondary school in Hulu Langat, Selangor. The respondents were selected using randomised cluster sampling among Form Four and Form Five students. Students were given self-administered questionnaire, consisting socio-demographic data and questions on their help-seeking barrier and behaviour. Help-seeking behaviour questions assess the use of medical facility and help-seeking sources. The formal helpseeking sources include from teachers, counsellors and doctors. The informal help-seeking sources include from friends, parents and siblings. Results: A total of 175 students were included in the study. None of the students admitted of using the primary health care services for their mental health problems. Majority of the students were not aware of the services availability in the primary health care (97.1%). More than half of them thought the problems were due to their own mistakes (55.4%) and the problems were not that serious (49.1%). With regard to perception of the primary health care services, (43.2%) of the students were worried about confidentiality, half of them were concerned about other people’s perception especially from their family members (44.6%) and friends (48.6%). Minority of them (10.8%) thought that nobody can help them. Few of them thought smoking (3.4%), alcohol (3.4%) and recreational drugs (1.1%) can solve their emotional problems. Conclusion: One of the major barriers identified in the students’ failure to use the health care facilities was their unawareness of the availability of the service for them in the community. Thus there is a need to promote and increase their awareness on this issue.